This preview shows page 1. Sign up to view the full content.
Unformatted text preview: p ( x ) = ( x 32 x + 1) (13 x 22 x1 )( x 32 x + 1)(13 x 22 x1 ) (13 x 22 x1 ) 2 = (3 x 22)(13 x 22 x1 )( x 32 x + 1)(6 x + 2 x2 ) (13 x 22 x1 ) 2 3. Find m by plugging x = 1 into p ( x ): m = p (1) = (1)(4)(0)(4) (4) 2 =4 16 =1 4 4. Find f (1) by plugging x = 1 into p ( x ): p (1) =4 = 0. 5. Using the slope m =1 / 4 and the point (1 , 0), nd the equation of the line with the point slope formula: yy 1 = m ( xx 1 ) which gives y =1 / 4( x1)....
View
Full
Document
This note was uploaded on 03/05/2012 for the course MATH 102 taught by Professor Davidscheinker during the Spring '12 term at Drexel.
 Spring '12
 DavidScheinker
 Derivative

Click to edit the document details